2004
DOI: 10.1016/j.nima.2003.11.332
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-engineered single-photon spectrometer for UV/visible detection

Abstract: We present predictions for a diffusion-engineered, single-photon spectrometer in the UV-visible range using a superconducting tunnel junction. Quasiparticles are created by photoexcitation, with charge Q 0 . After tunneling through the junction, the quasiparticles can either backtunnel or diffuse away. With confinement by a higher gap or by narrow leads the quasiparticles in the counterelectrode dwell next to the junction and backtunnel, increasing the collected charge to Q ¼ pQ 0 ; p>1. For very narrow leads … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…The loss mechanism is assumed to be uniform within the electrodes and the wire. Previously [7] we found that a good approximation to the 2-D simulation is the steady-state 1-D diffusion result, where the outdiffusion time is: (1) where is the effective Al area, and are the wire length and width, and is the quasiparticle diffusion constant in Al. This result diverges from the 2-D simulation as the time to reach steady-state in the wire becomes longer.…”
Section: Resultsmentioning
confidence: 95%
“…The loss mechanism is assumed to be uniform within the electrodes and the wire. Previously [7] we found that a good approximation to the 2-D simulation is the steady-state 1-D diffusion result, where the outdiffusion time is: (1) where is the effective Al area, and are the wire length and width, and is the quasiparticle diffusion constant in Al. This result diverges from the 2-D simulation as the time to reach steady-state in the wire becomes longer.…”
Section: Resultsmentioning
confidence: 95%
“…Segall 10 and Savu et al 11 developed a model for DROIDs which included the processes inside the STJs but assumes perfect trapping. Den Hartog et al 12 produced a twodimensional diffusion model of a DROID without trapping but accounting for quasiparticle dynamics in the STJ using Rothwarf-Taylor equations.…”
Section: Introductionmentioning
confidence: 99%
“…Superconducting Tunneling Junctions STJs are being developed as spectro-photometers in wavelengths ranging from the NIR to X-rays in different groups [1,2]. A pixelated 10 Â 12 array of STJs has already successfully been used as an optical imaging spectrometer, SCAM-3, for ground-based astronomy [3].…”
Section: Introductionmentioning
confidence: 99%